P134 Modified uvulopalatopharyngoplasty and radiofrequency-in-saline tongue in the management of snoring. (7th October 2021) - Lindsay, B; Sideris, A; Sarkis, L; Lam, M; Mackay, S
Abstract: Objective: The modified uvulopalatopharyngoplasty has not been investigated as an option in primary snoring. The aim of this study was to determine whether combined palatal and tongue surgery to enlarge and stabilize the upper airway is an effective treatment for patients with primary snoring who cannot tolerate or decline device therapy. Study design: This was a retrospective cohort study, and included adult patients with primary snoring who underwent modified uvulopalatopharyngoplasty and radiofrequency-in-saline tongue between January 2009 and December 2020. Patients with clinically significant obstructive sleep apnoea were excluded. Setting: Single centre study, based in New South Wales, Australia. Methods: Primary outcome measures were the Snoring Severity Scale (a questionnaire, which indicates loudness and frequency of snoring) completed both prior to and following surgery, and the Epworth Sleepiness Scale. Mean questionnaire scores prior to and at three-month follow-up were analysed. Results: 97 adult patients underwent upper airway surgery for simple snoring, of which 68 were included in the present study (37.3 ± 11.5 years, n=17 female). The mean SSS prior to surgery was 7.0 ± 1.6 and 1.9 ± 2.3 at 3-month follow up (P < 0.0001).The mean ESS prior to surgery was 9.0 ± 4.8 and 4.1 ± 2.8 at 3-month follow up (P <0.0001). Conclusion: The results of this study indicate that modified uvulopalatopharyngoplasty with radiofrequency-in-saline tongue is an effective treatment modality with a low complication rate. This procedure should be offered to carefully selected patients with primary snoring who have failed or declined device therapy.